2003
DOI: 10.1007/s00213-002-1335-4
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects in various mice strains in the forced swimming test

Abstract: Our study showed that drug sensitivity is genotype dependent. FST results have shown that Swiss mice are the most sensitive strain to detect 5-HT and/or NA treatment. The use of DBA/2 inbred mice may be limited, as an absence of antidepressant-like response was observed in the FST. The lack of sensitivity to antidepressant treatment in DBA/2 strains could be due to high DA, NA and 5-HT whole brain concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
97
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 37 publications
17
97
3
1
Order By: Relevance
“…Some authors have postulated that it is the high brain dopamine level in this strain that is a limiting factor for the antidepressant-like effects of ADs in this test (Renard et al, 2004). However, in our hands, WT animals were responsive to the acute and repeated administration of the antidepressants used in the present study, with the exception of citalopram, which was not effective, similar as in the studies reported by David et al (2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some authors have postulated that it is the high brain dopamine level in this strain that is a limiting factor for the antidepressant-like effects of ADs in this test (Renard et al, 2004). However, in our hands, WT animals were responsive to the acute and repeated administration of the antidepressants used in the present study, with the exception of citalopram, which was not effective, similar as in the studies reported by David et al (2003).…”
Section: Discussionsupporting
confidence: 87%
“…The strain of mice strongly influences the animal response in the FST (Alcaro et al, 2002;David et al, 2003;Lucki et al, 2001), with C57BL/6J mice being moderately responsive to ADs in this test. Some authors have postulated that it is the high brain dopamine level in this strain that is a limiting factor for the antidepressant-like effects of ADs in this test (Renard et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Ambiguous results concerning the sensitivity of DBA/2 mice towards the effects of antidepressants were reported. Some studies found the DBA/2 strain to be antidepressant-sensitive (Lucki et al 2001;Crowley et al 2005), whereas others did not (David et al 2003;Cervo et al 2005). The underlying reasons for this discrepancy still remain to be determined.…”
Section: Slc25a18mentioning
confidence: 95%
“…The FST and testing in the dark/light box were performed 4 h after last application in order to confirm the behavioral effects of the treatment at the same time point when the brains of test-naïve-treated mice were taken for microarray analysis. The mHB was performed 30 min after last application as many published results on behavioral effects of antidepressants were assessed at this time point (e.g., Lucki et al 2001;David et al 2003;Crowley et al 2005).…”
Section: Behavioral Testingmentioning
confidence: 99%
“…The forced swimming test was performed according to the method described previously [22] . Mice were put singly into transparent Plexiglas cylinders (height: 24 cm, diameter: 13 cm) containing water at a depth of 10 cm, maintained at 22 °C for 6 min.…”
Section: Forced Swimming Test (Fst)mentioning
confidence: 99%